Welfare and Market Impacts of Food Safety Measures in China: Results from Urban Consumers' Valuation of Product Attributes - David L. Ortega; H. Holly Wang; Nicole J. Olynk Widmar (Journal of Integrative Agriculture, 2014)
This study provides an economics assessment of various food safety measures in China. A choice experiment approach is used to elicit Chinese consumer preferences for various food safety attributes using data from a 2008 urban consumer survey. An alternative welfare calculation is used to model aggregate market impacts of select food safety measures. Our results show that the largest welfare gains are found in the current government-run certification program. The implementation of a third-party certification system, a traceability network and a product label would generate significant value and would help reduce current system inefficiencies in China. This study builds on previous research and provides an alternative approach for calculating consumer valuation of safety and quality attributes that can be used to estimate aggregate economic and welfare impacts.